Exploring the bereavement experiences and prevalence of prolonged grief disorder among 2023 Turkish earthquake survivors with advanced chronic disease: a mixed methods study - Ismail Toygar; Çiğdem Fulya Dönmez; Serpilay Mum (BMJ Open)
Objective While traumatic experience of a loved one’s death and having a chronic disease are both risk factors for prolonged grief disorder, there are no published studies on bereavement among earthquake survivors with advanced chronic disease. The objective of this study is to explore the bereavement experiences and prevalence of prolonged grief disorder (PGD) among 2023 Türkiye earthquake survivors with advanced chronic diseases.Design/setting A mixed methods design of cross-sectional survey using the Prolonged Grief Scale (PG-13) and semi-structured interviews was used to provide a detailed understanding of the grief phenomenon in the context of bereaved adults with advanced chronic disease after the earthquake in Türkiye.Participants 143 participants completed the survey, and interviews were conducted with 12 bereaved survivors with advanced chronic disease.Results Our results indicated a prevalence of PGD among bereaved adults of 23.8%. The traumatic death of first-degree relatives was associated with a higher PGD prevalence (p<0.001). PGD developed in 50% of retirees (n=6). Six themes were identified: (1) bereavement reactions, (2) coping style, (3) disrupted grieving, (4) impact of grief on chronic disease, (5) moving forward and (6) unmet needs.Conclusions We recommend a person-centred bereavement care that prioritises early identification and reduction of prolonged grief risk factors. We propose a framework for bereaved survivors to use in the development of an effective bereavement service model. This model may be used by mental health professionals and policymakers to respond sensitively to the values, needs and preferences of bereaved survivors who have experienced the unnatural death of a loved one.